Research on stability of steep bank slope and reserved thin-walled rock cofferdam during excavation of intake foundation pit. (November 2022) - Wang, Kezhong; Gao, Yaohui; Jin, Zhihao; Zhou, Xin; Chen, Liehao; Zhang, Chun
Highlights: Various engineering risks of high and steep slope near river and reservoir are analyzed. In view of various risks during excavation of the foundation pit near high and steep slope, several effective reinforcement measures are proposed. The finite difference software FLAC 3D is used to simulate the evolution process of slope deformation, and the deformation law of steel tubular pipe pile is analyzed. The plastic deformation law of reserved thin-walled rock wall is studied, and the stress characteristics of support beam in foundation pit are found. Abstract: The intake of water diversion project is generally located on the bank slope above the large reservoir or deep water area of a river. Due to the influence of water level change and hydraulic action, the rock mass of bank slope is seriously weathered and broken, leading that the rock mass has low strength and is easy to collapse or landslide. In this paper, the water intake engineering of the long-distance diversion project in central Shanxi Province is selected as the research object. The multi-point displacement meter is used to monitor the slope deformation after anchorage and concrete retaining wall support. Based on the FLAC 3D V6.0 software, the numerical simulation of the excavation process of the steep reinforced river bank slope is carried out, and the long-term deformation of the slope is predicted. The excavation scheme of retaining outer thin-walled rock wall as water cofferdam is proposed. The excavation process of foundation pit, which is supported with concrete-filled steel tubular pile reinforcing cofferdam and concrete supporting beam, is simulated. It is found that the upper part of the steep slope supported by anchor cable and concrete retaining wall is stable, and the large deformation and plastic failure of the water-retaining thin rock wall are mainly affected by the disturbance of foundation pit excavation. The concrete-filled steel tubular pile support avoids the collapse of the reserved thin-walled cofferdam, and the horizontal beam in the foundation pit improves the stress state of the external wall of the foundation pit. The research results of this paper reveal the evolution mechanism of rock mass deformation and failure during excavation of foundation pit on steep bank slope, and provide guidance for excavation and support of foundation pit for similar bank slope.